Collaborative speculation: Anticipation, inclusion and designing counterfactual futures for appropriation. (December 2021) - Light, Ann
Highlights: Describes a process for speculating on futures using the past. Draws on counterfactuality and the logics of cause and effect. Contrasts stimuli for speculation such as scenarios, stories and seeds. Offers a bottom-up democratizing politics in the design of workshop activities. Explores the methodology in sufficient detail to replicate. Abstract: How do people become conversant with futures-in-the-making? This paper explores speculative design from the position that futures have agency in the present and therefore forms of speculation – as well as futures - need to be inclusive. Regarding this as a democratic right throws attention on engagement processes, noting that speculation is often centred on the designer's interests rather than seeding appropriation by publics. I argue that situating speculation in a way that is accessible for negotiation requires careful attention to the hybrid process + object artifacts that result from designing both a provocation and a process for encountering it. My central case study describes one such hybrid artifact, a counterfactual workshop for considering futures by exploring different imagined pasts and making a journey towards alternative presents. This play of temporalities – and the accompanying methods for opening and narrowing the creative work of taking these journeys – suggest a means that speculative design might be situated with participants, thereby simultaneously reflecting on and mitigating the anticipatory nature of the materials. I deconstruct this instance of curating speculative artifacts to reveal not only its mechanisms, but the many points where engagement processes reflect political choices.